Cephalometric Characteristic of Skeletal Class II Malocclusion in Javanese Population at Universitas Airlangga Dental Hospital - I Gusti Aju Wahju Ardani (Wolters Kluwer - Medknow, 2018)
Introduction: To describe the cephalometric characteristic of skeletal Class II malocclusion in Javanese Population at Universitas Airlangga Dental Hospital. Methods: A total of 118 lateral cephalograms of preorthodontic patients with skeletal Class II malocclusion were obtained from Universitas Airlangga Dental Hospital. The lateral cephalograms were analyzed using digital cephalometric analysis to determine the ANB, mandibular length, facial axis, Y‑axis, sella to nasion‑mandibular plane (SN‑MP), and lower anterior facial height (LAFH). Correlation between mandibular length and other variables was analyzed using Pearson correlation test with P < 0.05. Results: There was an increase of ANB, Y‑axis, SN‑MP, and LAFH. While SNB was decrease and mandibular length was shortened. There was a significant correlation between mandibular length and other variables, such as facial axis, SN‑MP, LAFH, and ANB. Conclusions: Skeletal Class II malocclusion in Javanese Population at Universitas Airlangga Dental Hospital was characterized by short mandibular length and large ANB mostly not by the increased of SNA but by the lack of SNB. The length of mandible correlated with facial axis angle, lower anterior facial height, and mandibular plane angle.